PENGARUH REAL EARNING MANAGEMENT DAN ECONOMIC VALUE ADDED TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS LABA SEBAGAI VARIABEL INTERVENING (PADA PERUSAHAAN SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2014 – 2017) - Makmuri Ahdi (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2020)
This research was conducted to determine the effect of Economic Value Added and Real Earnings Management toward the firm value with Earnings Quality as an intermediary. This research was conducted on manufacturing companies on the Indonesia Stock Exchange in 2014 - 2017. The analytical method used the Two Stage Least Square method (2SLS). This research used SPSS version 23. The result of this research Real Earning Management has a negative and sinificant influence on earnings quality (H0 rejected, H1 accepted). This is showed with a significance value of 0.013 under at a significance level of 5%. Economic Value Added has influence not significant with the confidence level of 89% on earnings quality. Real Earnings Management has not affecton earnings quality with a standardized coefficient beta or a level of influence of 12.3% with the direction of a positive relationship. Earning quality has a positive and significant with a cinfidence level of 99.98% of the firm value. Earning quality has a significant effect on firm value with a standardized coefficient beta or a level of influence of 12.3% with the direction of a positive relationship. Real earning managementhas influence not significant with a confidence level of 17.5% of the firm value. Real earnings management does not affect the firm value with with a standardized coefficient beta or the level of influence of 1.6% with the direction of a positive relationship. Economic value added has a significant effect on the confidence level of 100% of the firm value. Economic value added influences the firm value with aastandardized coefficient betaor an influence level of 31% with the direction of a positive relationship.